2017
DOI: 10.4236/jep.2017.811086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co-Existing Ions on the Phosphorus Potassium Ratio of the Precipitate Formed in the Potassium Phosphate Crystallization Process

Abstract: Livestock wastewater is mainly treated with activated sludge, but ions such as phosphorus, potassium, ammonium, nitrate and sulfate remain in the effluent. In this study, the effects of residual ions on phosphorus recovery using the magnesium potassium phosphate crystallization method were investigated when magnesium was added to increase the pH. If co-existing ions affect the products, the phosphorus to potassium molar ratio (K/P ratio) of the precipitate will deviate from being equimolar. Artificial wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Their model outputs also pointed out a significant drop in K recovery efficiency above pH 11. Harada et al [55] found that in MPP precipitation, K removal efficiency was reduced as the pH was increased from 11 to 12.…”
Section: Operation Phmentioning
confidence: 99%
“…Their model outputs also pointed out a significant drop in K recovery efficiency above pH 11. Harada et al [55] found that in MPP precipitation, K removal efficiency was reduced as the pH was increased from 11 to 12.…”
Section: Operation Phmentioning
confidence: 99%
“…Due to easy management was used in many studies through which the kinetics of the nucleation process have been assessed [19,20]. While the pH was maintained in alkaline condition of 11 which following based on [21]. Since the conditions favorable precipitation of struvite-K. Based on Figure 2 shows that P removal rate was decreased from 98.5-80% which increasing of molar ratios of Mg:P from 0.8 to 1.22 since strong influence of precipitation in many scientist [22].…”
Section: Effect Different Initial Of Mg:p Ratios On % P Removal and Precipitatementioning
confidence: 99%
“…The determination of the variation in the addition of the Mg dosages has been decided: 5 mmol/l, 10 mmol/l, 15 mmol/l. Then from previous research [17] that pH 11 has been selected as the best treatment for increasing pH. After the filtrate is formed, it is weighed and dissolved in 1 mol/L of H 2 SO 4 and the concentration is measured using atomic absorption spectrometry (AAS) (Shimadzu AA-6300).…”
Section: Effect Of Increasing Ph and Mg Dosages In The Syngenite Formationmentioning
confidence: 99%
“…The SO 4 ion in solution tends to prevent the smooth process of Ca inhibition against K. Because it has been explained in Harada's research [17] that they concluded that sulfate is not included as a compound containing sulfur in crystals but is inhibited.…”
Section: Effect Of Increasing Ph and Mg Dosages In The Syngenite Formationmentioning
confidence: 99%
See 1 more Smart Citation